Estimation Precipitable Water Vapor Using (PWV) The Permanent Single GPS Station in Makasar and Bitung, Indonesia - Syachrul Arief (Politeknik Negeri Batam, 2022)
Meteorological investigations using global positioning systems (GPS) are based on permanent networks that are expensive to develop globally on Earth. In this study, it was confirmed that a single station GPS meteorology was feasible where there was no possibility for the development of a sophisticated, reliable GPS network. In Sulawesi, there are several GPS stations since 2009 GPS stations have been installed in Makassar and Bitung by the Indonesian Geospatial Information Agency, in which meteorological sensors are also installed in the station. GPS data is processed to estimate the total zenith delay (ZTD) of GPS signals in the troposphere. The ZTD estimate is then automatically converted to stored water vapor (PWV) using goGPS software. Two types of validation were applied to the PWV estimation. All of them proved the validity of the GPS results: (1) PWV was measured using radiosondes in Makassar and Bitung with almost the same climate regime, each showing a correlation of 96.5 and 83.0% with GPS PWV time series. (2) a global reanalysis dataset was showing correlations of 60.1 and 75.3%, respectively, with GPS results. This validation shows that a permanent GPS network can be an alternative to get temporally more detailed and accurate meteorological data and lower costs and time-saving operations.